Profesionalisme Guru Perspektif Peraturan Pemerintah No. 19 Tahun 2005 - Pristiwiyanto Pristiwiyanto (THE JOER: Journal Of Education Research, 2021)
Teacher professionalism and competence is a skill or ability that must be possessed by an educator or teacher in order to carry out their duties and responsibilities properly. As an educator or teacher, you are required to have professionalism and competence. If an educator or teacher does not have competence and professionalism in himself, then an educator or teacher will not be competent in carrying out his duties. Professional competence is one of the competencies that every educator or teacher must possess. The importance of developing professional competence will show the quality of the performance results of a teacher or educator. The development of these competencies can be done by attending discussion meetings, reading books, and attending seminars. The purpose of this study was to find out how the teacher's efforts in developing professional competence. This study uses a qualitative approach with the methods of observation, interviews, and documentation. The results of the study show that efforts to increase teacher professionalism and competence will also increase the insight of a teacher, be more responsible and more professional in improving teaching and learning tasks inside and outside the classroom.